Oxytoma octavia - Hryniewicz, Krzysztof; Little, Crispin T. S.; Nakrem, Hans Arne (Zenodo, 2014)
Oxytoma octavia (d’Orbigny, 1850) (Figure 10 C–G ) 1850 Avicula Octavia sp. nov.—d’Orbigny, p. 61. 1984 Oxytoma ( Oxytoma ) octavia (d’Orbigny) —Kelly, p. 61, pl. 5, figs. 1–9 and references therein. 2011 Oxytoma sp. — Hammer et al . 2011, fig. 7q, tab. 2. Material. 37 specimens, all single valves with completely or partially preserved shells. Four right valves, 33 left valves. See Appendix 1 for the list of specimens. Dimensions. 7–24.5 mm in length, 7–23.5 mm in height. See Figure 11 A–C and Appendix 2F for details. Description. Adult shell more than 24 mm long, inequivalved with left valve significantly larger than right. Left valve oval and weakly posteroventrally elongated; thin, inequilateral, moderately inflated, ornament of 15–20 radial primary ribs, intercalated with secondary riblets and occasionally very weak tertiary riblets. Primary radial ribs dense, but thin, on early shell growth stages, progressively thicker during ontogeny. On internal moulds ribs visible only on later growth stages. Inter-rib spaces around five times wider than primary ribs. Secondary ribs appear on shell in late growth stages, but on internal moulds are present only on ventral margins of larger specimens. Ribs occasionally show disturbances and deflections. Shell growth lines weak; no nodes present at radial ribs intersections. Beak weakly prosogyrate, hinge line straight. Posterior auricle present; in investigated specimens not projecting beyond posterior valve margin, demarcated from the rest of valve by weak, oblique sulcus. Anterior auricle absent, groove in inner shell surface below anterior part of hinge line visible on outer shell surface as an oblique, elongated ridge. Right valve thin, circular to weakly oval in outline; inequilateral, flat to weakly inflated. Radial ribs present on external shell surface, absent on internal moulds. Beak weakly prosogyrate, hinge line straight, posterior auricle moderately long, projecting beyond posterior valve margin; indistinct sulcus demarcating auricle from rest of valve. Anterior auricle straight, triangular, acute, around a fifth to a sixth of hinge line length. Triangular and moderately deep byssal notch developed below anterior auricle, with main axis slightly oblique to the hinge line. Ctenolium not observed. Remarks. Our specimens are synonymized with Oxytoma octavia (d’Orbigny, 1850) due to their strong secondary ribs on the right valve, which is markedly smaller than the left valve. Oxytoma octavia is inequivalved and characterized by having 12 to 20 primary ribs on the left valve (12 to 19 in Kelly 1984, p. 62), separated by distinct secondary and tertiary riblets (e.g. Kelly 1984, text-fig. 40). The rather similar O. inequivalve (J. Sowerby, 1819), widespread from the Lower Jurassic up to the Kimmeridgian (e.g. Gerasimov 1955; Ichikawa 1958; Cox 1965; Duff 1978; Wierzbowski et al. 1981; Pugaczewska 1986; Clausen & Wignall 1990) has a left valve with a similar number of radial ribs to O . octavia and with inter-rib spaces containing variably strong secondaries and tertiaries (e.g. Duff 1978, p. 55). The difference between O. octavia and O. inequivalve lies in the presence of primary and secondary ribbing on the right valve in O . octavia contrasting with the smooth or weakly striated right valve of O . inequivalve (Duff 1978; Kelly 1984). The right valves of our specimens are small and circular, which suggests an inequivalve condition, separating our species from O. expansa (Phillips, 1829) which is approximately equivalved (e.g. Arkell 1931, p. 191). Our specimens are much less inequilateral and have a very different style of ribbing than O. ( Boreioxytoma ) aucta Zakharov, 1966, from the Volgian of Siberia (Zakharov 1966), which has seven to nine widely spaced primary ribs (Zakharov 1966, pl. I: 6, pl. II:1). Occurrence. Seeps 3, 5, 8 and 9 (Upper Volgian–uppermost Ryazanian), Slottsmøya Member, Svalbard (Tab. 1). Occurs in the Volgian–Ryazanian of Europe, Greenland, Russia and Siberia (de Loriol & Pellat 1867; Lewinski 1922; Spath 1936; 1947; Gerasimov 1955; Zakharov 1966; Fürsich 1982; Birkenmajer et al. 1982; Kelly 1984). Palaeoecology. Oxytoma octavia was a byssally attached filter feeder. This mode of life is shared by many other pteriomorphs (Stanley 1970). The long posterior auricle likely sheltered the posterior exhalant current from being swept back into the shell by water currents, as in pteriids (Stanley 1970). Because of the relatively thin valves, O. octavia was more likely preserved in less agitated environments, where it was living attached to loose shells and local carbonate hardgrounds. A pseudoplanktonic mode of life and attachment to drifting algal fronds is also possible for O. octavia , an interpretation supported by the lack of articulated specimens in the studied material. : Published as part of Hryniewicz, Krzysztof, Little, Crispin T. S. & Nakrem, Hans Arne, 2014, Bivalves from the latest Jurassic-earliest Cretaceous hydrocarbon seep carbonates from central Spitsbergen, Svalbard, pp. 1-66 in Zootaxa 3859 (1) on pages 23-25, DOI: 10.11646/zootaxa.3859.1.1, http://zenodo.org/record/4930112 : {"references": ["Hammer, O., Nakrem, H. A., Little, C. T. S., Hryniewicz, K., Sandy, M., Hurum, J. H., Druckenmiller, P., Knutsen, E. M. & Hoyberget, M. (2011) Hydrocarbon seeps from close to the Jurassic - Cretaceous boundary, Svalbard. Palaeogeography, Palaeoclimatology, Palaeoecology, 306, 15 - 26. http: // dx. doi. org / 10.1016 / j. palaeo. 2011.03.019", "Kelly, S. R. A. (1984) Bivalvia of the Spilsby Sandstone and the Sandringham Sands (Late Jurassic - Early Cretaceous) of Eastern England. Part 1. Palaeontographical Society Monographs, 137, 1 - 94, pls. 1 - 20.", "Sowerby, J. (1819) The Mineral Conchology of Great Britain 3 (2), J. Sowerby, London, 41 - 98, pls. 222 - 253. http: // dx. doi. org / 10.5962 / bhl. title. 14408", "Gerasimov, P. A. (1955) Index fossils of Mesozoic of the central regions of the European part of the USSR. Part I. Lamellibranchiata, Gastropoda, Scaphopoda and Brachiopoda from the Jurassic deposits. Gosgeoltekhizdat, Moscow, 274 pp., 50 pls. [in Russian]", "Ichikawa, K. (1958) Zur Taxonomie und Phylogenie der triadischen \" Pteriidae \" (Lamellibranch.) mit besonderer Berucksichtigung der Gattungen Claraia, Eumorphotis, Oxytoma und Monotis. Palaeontographica (A), 111, 131 - 212, pls. 21 - 24.", "Cox, L. R. (1965) Jurassic Bivalvia and Gastropoda from Tanganyika and Kenya. Bulletin of the British Museum (Natural History), Supplement 1, 1 - 209, pls. 1 - 30.", "Duff, K. L. (1978) Bivalvia from the English lower Oxford Clay (Middle Jurassic). Palaeontographical Society Monograph s, 132, 1 - 137, pls. 1 - 13.", "Wierzbowski, A., Kulicki, C. & Pugaczewska, H. (1981) Fauna and stratigraphy of the Uppermost Triassic and the Toarcian and Aalenian deposits in the Sassenfjorden, Spitsbergen. Acta Palaeontologica Polonica, 26, 195 - 241, pls. 1 - 11.", "Pugaczewska, H. (1986) Bivalvia of the Polish Middle Jurassic and remarks on their paleoecology. Acta Palaeontologica Polonica, 31, 27 - 83, pls. 15 - 34.", "Clausen, C. K. & Wignall, P. B. (1990) Early Kimmeridgian bivalves of southern England. Mesozoic Research, 2, 97 - 149.", "Phillips, J. (1829) Illustrations of the geology of Yorkshire. 1 st edition. Printed for John Murray, Ablemarle Street, York, xvi + 192 pp., 24 pls.", "Arkell, W. J. (1931) British Corallian Lamellibranchia. Part V. Palaeontographical Society Monographs, 88, 181 - 228, pls. 21 - 28.", "Zakharov, V. A. (1966) Late Jurassic to early Cretaceous bivalve mollusks of northern Siberia. Nauka, Moscow, 189 pp, 38 pls. [in Russian]", "Loriol, P. de & Pellat, A. (1867) Monograpie paleontologique et geologique de l'etage Portlandien des environs de Boulognesur-Mer. Memoires de la Societe de Physique et d'Histoire naturelle de Geneve, 19, 1 - 200, pls. 1 - 11.", "Lewinski, J. (1922) Monographie geologique et paleontologique du Bolonien de la Pologne. Memoires de la Societe Geologique de France, 56, 1 - 56, pls. 1 - 8.", "Spath, L. F. (1936) The Upper Jurassic invertebrate faunas of Cape Leslie, Milne Land. II. Upper Kimmeridgian and Portlandian. Meddelelser om GrOnland, 99, 1 - 180, pls. 1 - 50.", "Spath, L. F. (1947) Additional observations on the invertebrates (chiefly ammonites) of the Jurassic and Cretaceous of East Greenland. I. The Hectoroceras fauna of the S. W. Jameson Land. Meddelelser om GrOnland, 132, 1 - 69, pls. 1 - 5.", "Fursich, F. T. (1982) Upper Jurassic bivalves from Milne Land, East Greenland. GrOnlands Geologiske UndersOgelse, 144, 1 - 126.", "Birkenmajer, K., Pugaczewska, H. & Wierzbowski, A. (1982) The Janusfjellet Formation (Jurassic - Lower Cretaceous) at Myklegardfjellet, east Spitsbergen. Palaeontologia Polonica, 43, 107 - 140, pls. 37 - 46.", "Stanley, S. M. (1970) Relation of shell form to life habits of the Bivalvia (Mollusca). The Geological Society of America Memoir, 125, 1 - 296. http: // dx. doi. org / 10.1130 / mem 125 - p 1"]}